2022
DOI: 10.1155/2022/2135487
|View full text |Cite
|
Sign up to set email alerts
|

Reineckia carnea Alleviates the Production of Inflammatory Cytokines and MUC5AC in Rats with Chronic Obstructive Pulmonary Disease

Abstract: Background. Reineckia carnea (RC), a perennial evergreen herb which belongs to Reineckia Kunth (Liliaceae), can be used for clearing the lungs and relieving cough, reducing phlegm and anti-inflammatory effects. Moreover, chronic obstructive pulmonary disease (COPD) is characterized by airway and lung inflammation and increased secretion of airway mucus. Therefore, RC has the potential to treat COPD. Methods. NR8383 cells were cultured and treated with various concentrations of RC (100 mg/mL, 10 mg/mL, 1 mg/mL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Studies had shown that CYP1A1 [71] and AGTR2 [72] were associated with heart failure. CYP1A1 [73], HHIP (hedgehog interacting protein) [74], MUC5AC [75] and CYP2A6 [76] might be a potential therapeutic targets for chronic obstructive pulmonary disease treatment. Previous studies have reported that the CYP1A1 [77], MUC5AC [78] and ATP12A [79] are a key regulator of airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies had shown that CYP1A1 [71] and AGTR2 [72] were associated with heart failure. CYP1A1 [73], HHIP (hedgehog interacting protein) [74], MUC5AC [75] and CYP2A6 [76] might be a potential therapeutic targets for chronic obstructive pulmonary disease treatment. Previous studies have reported that the CYP1A1 [77], MUC5AC [78] and ATP12A [79] are a key regulator of airway inflammation.…”
Section: Discussionmentioning
confidence: 99%